Kemasukan tenaga kerja Indonesia ke Malaysia semasa pemerintahan Tun Dr. Mahathir bin Mohamad dan kini - Azed, Abdul Bari (2014)
Malaysia has experienced a significant change in economic structure since independence in 1957. The strategy and the industrial policy initiated in the early 1960s, have transformed Malaysia from an agro-based country to an industry and services-based country. Under the leadership of Tun Dr. Mahathir bin Mohamad, Malaysia transformed into a development centre for high-tech manufacturing, finance and smart telecommunication. Through several economic policies introduced during his period, mega- construction projects were carried out. All the planning and implementation of these projects required a workforce, especially skilled and unskilled, particularly in the construction sector. One of the policies that was implemented to support the needs of this workforce was to bring in foreign workers from various countries including Indonesia. Although various immigration rules have been introduced to control the migration of Indonesian workers, economic factors have influenced the influx of Indonesian workers to come to Malaysia. Therefore, the main objective of this research is to study the policies of the Malaysian and the Indonesian governments during the era of Tun Dr Mahathir Bin Mohamad, related to Indonesian workers, to understand both governments’ decision- making process in recruiting Indonesian workers as well as to identify the implications of the recruitment policy of the Indonesian workers . The data for this research was obtained through the Malaysian and Indonesian Immigration departments, the Embassy of the Republic of Indonesia and the National Agency for the Placement and Protection of Indonesian Workers in Indonesia. This case study involved interviews with Malaysian and Indonesian leaders. The data analysis was made by comparing the similarities and the differences stated in the answers given. The study found that the recruitment of Indonesian workers in Malaysia was a condition that was difficult to contain in the era of globalization. The question was how could the migration provide positive implications in terms of the economic, political and social development of both countries. In order to address the problems that arise with Indonesian workers in Malaysia, both countries should be committed and work together to find solutions for the workforce-related issues as they cannot be resolved through the role of only one country.